Mesoporous SBA-15 Silica–Loaded Nano-formulation of Quercetin: A Probable Radio-Sensitizer for Lung Carcinoma. Issue 1 (13th January 2022) - Alkahtani, Saad; Alarifi, Saud; Aljarba, Nada H.; Alghamdi, Hamzah A.; Alkahtane, Abdullah A.
Lung cancer is considered as one of the most serious disease worldwide. The progress of drug carriers based on nonmaterial, which selectively hold chemotherapeutic agents to cancer cells, has become a major focus in biomedical research. This study aimed to evaluate the growth inhibition and apoptosis induction of the human lung cancer cells (A-549) by Q-loaded SBA-15 conjugate system. Mesoporous silica nanoparticles (SBA-15) as host materials for transporting therapeutics medicaments were fabricated for targeted drug delivery toward lung cancer. With the objective of increasing bioavailability and aqueous solubility of flavonoids, SBA-15 was successfully loaded with the quercetin (Q)—a major flavonoid and characterized with the help of Fourier-transform infrared spectroscopy (FTIR) and transmission electron microscopy (TEM). The biological investigation on A549 cell line confirmed that the efficacy of Q-SBA-15 is much higher than only Q. Moreover, the apoptotic pathway of synthesized Q-SBA-15 NPs examined that the Q-SBA-15–mediated apoptosis via PI3K/AKT/mTOR signaling pathway. Thus, the newly conjugated Q-SBA-15 system improved the apoptotic fate through caspase-mediated apoptosis via PI3K/AKT/mTOR signaling pathway and hence, it can be potentially employed as an anticancer agent for lung cancer.